Peran dan Tanggung Jawab Notaris dalam Penyelesaian Sengketa Perdata di Indonesia Melalui Akta Notaris - Ayu Cahya Widianingrum; Siti Malikhatun Badriyah (Pusat Riset dan Inovasi Nasional, 2025)
This article examines the role and responsibility of notaries in resolving civil disputes in Indonesia through notarial deeds. Notaries play a crucial role as officials authorized to create authentic deeds that provide legal certainty and serve as strong evidence in civil legal processes. This study employs a literature review method by analyzing various legal sources, journals, and regulations related to notarial practice and dispute resolution. The findings reveal that notarial deeds function not only as the basis for agreements but also as primary instruments in effectively resolving legal conflicts. However, notaries face several challenges, including limited public understanding, external pressures, and rapid technological developments. Therefore, strengthening regulations, enhancing notary competence, utilizing technology, and public education are essential to improve the role of notaries in ensuring legal certainty and dispute resolution. This study offers strategic recommendations to reinforce the notary's function as a cornerstone of Indonesia’s civil legal system.